Computational techniques for using insole pressure sensors to analyse three-dimensional joint kinetics - Chumanov, E. S.; Remy, C. D.; Thelen, D. G. (Computer Methods in Biomechanics and Biomedical Engineering, 2009)
This study evaluated the feasibility of using insole pressure sensors together with whole body dynamics to analyse joint kinetics while running. Local affine transformations of shoe kinematics were first used to track the position of insole sensors during locomotion. Centre of pressure estimates derived from the insoles were within 10 mm of forceplate measures through much of stance, while vertical force estimates were within 15% of peak forceplate recordings. Insole data were then coupled with a least squares whole body dynamic model to obtain shear force estimates that were comparable to forceplate records during running. We demonstrated that these techniques provide a viable approach for analysing joint kinetics when running on uninstrumented surfaces.